Kampanye Catcalling Pada Perempuan Di Media Sosial: (Analisis Wacana Kritis Pada Akun Instagram @dearcatcallers.id) - Nurfudiniyah; Lukman Hakim (Jurnal Ilmu Komunikasi, 2022)
Sexual harassment is an issue that has long been a social problem, especially in Indonesia. The number of sexual harassment cases is increasing every year and most of them are dominated by verbal sexual harassment such as catcalling. One of the social media that campaigns for the issue of catcalling is the Instagram account @dearcatcallers.id. This study discusses how the catcalling campaign for women on the Instagram account @dearcatcallerd.id. This study aims to find out the discourse behind the @dearcatcallers.id campaign content using Norman Fairclough's Critical Discourse Analysis. This study resulted in the finding that @dearcatcallers.id created and shared its content in response to harassment events that occurred in the form of survivor narratives or videos from third parties, not in the form of content that was intentionally made about catcalling. The story is rewritten or disseminated by emphasizing several meanings so that the essence of catcalling can be accepted by netizens. For example, making Bold Style writing, using exclamation points, emoticons, everyday language, and terms that have positive connotations.